Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Aftech Makassar Indonesia - Syam, Shofiana; Faisal, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to determine the effect of competence and work discipline on employee performance at PT. Aftech Makassar Indonesia. This study used 60 samples (respondents). Sources of primary data and secondary data. The data analysis method in this study used descriptive analysis and statistical analysis of validity test, reliability test, multiple regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of the descriptive analysis of competence obtained the actual score percentage of 89.3%, analysis work discipline obtained the percentage of the actual score of 89.5% and performance analysis obtained the percentage of the actual score of 91%. The results of statistical analysis obtained multiple linear regression coefficients, namely: Y = 18.933 + 0.263X1 + 0.333 X2, the correlation coefficient of competence to performance (r) = 0.393 and the correlation coefficient of work discipline to performance (r) = 0.469. And the coefficient of determination (r2) is 0.257 or 25.7%. The value of Fcount > Ftable (11,219 > 3.16) and through the partial test calculation (t-test) it is seen that H1 where the t-count value is greater than t-table (2,228 > 2.002 and the significance value is 0.030 < 0.05) and H2 where the t-count value of work discipline is greater than the t-table (3.186 > 0.05) and the significance value is 0.002 < 0.05). The results of this study indicate that competence and work discipline have a positive and significant effect on employee performance at PT. Aftech Makassar Indonesia, thus the hypothesis used is acceptable